EIN NEUES OPTISCHES MESSGERÄT ZUR MESSUNG DER GERADHEIT LANGER BOHRUNGEN - Turi, Z.; Ábrahám, Gy.; Halmai, A.; Huba, A.; Wenzel, K. (Periodica Polytechnica Mechanical Engineering, 1987)
The measurement of workpieces with long but smalldiametric cavitys (drills) is always adifficult problem. The apparatus shown in this paper has been developped for measurement ofthe straightness of cavitys with 5-10 mm diameter and 600-1000 mm length. The opticalprinciple of this measuring allows to achieve the uncertainty less then ± 5 11 qm.